EMPLOYEE PERFORMANCE EFFECTIVELY INFLUENCED BY MOTIVATION AND WORK DISCIPLINE - Mohammad Noor Khairullah (Journal of Innovation Research and Knowledge, 2023)
The purpose of this study was to determine the effect of work motivation and discipline on the performance of SMA NEGERI 1 TEMPEH Lumajang employees, either partially or simultaneously. The population in this study were all employees of SMA NEGERI 1 TEMPEH Lumajang. The number of samples in the study were 32 respondents. The sampling technique used is the census sample. The research method used is a quantitative research method using data analysis techniques used is multiple linear regression. Data collection method used in this study using a questionnaire. The results showed that the motivational variable did not have a partial significant effect on employee performance. Then for the work discipline variable it does not have a partial significant effect on employee performance. While simultaneously the variables of motivation and work discipline have a significant effect on employee performance. For SMA NEGERI 1 TEMPEH Lumajang, suggested that more often to provide motivation, especially for employees so that they can spur and encourage them to do a good job.